EFFICACY OF VAITARAN BASTI AND SIMHANAD GUGGUL IN AMAVATA - Wadhwa Ritu. S.; Ghore Jaya.K (International Journal of Applied Ayurved Research, 2015)
Amavata is an autoimmune disease & compared with Rheumatic arthritis.Vaitaran Basti is indicated to controle this disorder.To prove its efficacy in Amavata 10 patients were selected with classical symptoms of Amavata from Panchakarma OPD of Dr.D.Y.Patil school of Ayurved & Research Institute Nerul. First & last Saindhavadi tail matra basti of 50 m.l. was followed by 8 no. of vaitaran Basti.Total 10 Basti was administered. Simhanad guggul 500mg. twice in a day for 30 days was adviced as shaman aushadhi. Patients got significant result with these treatment.Vaitaran Basti